Study of the Instantaneous Water Level Measurement Method on Unsteady Flow Based on Single Camera and Fixed Scale Compensation in the Tunnel Model - Weihua Ding; Hu Li; Fan Yang; Bin Hou; Haibin Xue; Feihu Wang; Zongxiao Zhang; Xinhong Wang (Advances in Civil Engineering)
The shape of instantaneous water surface profiles for the unsteady flow in the tunnel model can be determined by measuring the instantaneous water levels at multiple points synchronously. However, the measurement accuracy of the ultrasonic method is affected greatly because of the complex state of the water surface when water level changes rapidly. Using an optical method, multicamera synchronous measurement is difficult to control, and the cost is high. For single camera measurement, the reading of the steel ruler in the image cannot be clearly seen when the distance between the measuring point and single camera is far. When the distance is short, all steel rulers cannot be captured at the same time. Hence, in this paper, a single camera and fixed scale compensation method for instantaneous water level observation in unsteady flow is proposed. A series of fixed scales is placed with the same height and width near the water surface to be measured. In order to capture dynamic images of all fixed scales with a clear water surface, a single camera is set at a far position to continuously record the water level change process within the model range. According to the height of the fixed scale, the image accuracy is compensated and the effect of the wide-angle image distortion is automatically avoided. The water level elevation is obtained according to the relationship between the fixed scale and the water surface. In this paper, the unsteady flow model measuring test is applied to the Southern Main Tunnel and the Water Distribution Pool of the Huangchigou Water Diversion Project. The accuracy of this method in measuring the dynamic water level is 1–2 mm, which meets the accuracy requirement and greatly reduces the observation cost of the model test. The proposed method may also be suitable for measuring the instantaneous water level of the unsteady flow in other similar hydraulic model tests.